A contribuição da empatia e da justiça nas estratégias de resolução de conflitos em moradias universitárias - Assis, Natália Lins Pequeno de (2022)
The purpose of this thesis was to verify whether the dimensions of empathy, combined with moral principles of justice, could explain the conflict resolution strategies that undergraduate students believed to adopt in situations of disagreements in the university housing where they lived. For the construction of this study, the thesis was structured in three empirical articles. The first article, of an exploratory nature, aimed to investigate to know the complaints on possible situations that trigger conflicts in university residents in a student housing, their perceptions about the habitation and if they resolve their conflicts. 60 residents were interviewed and it was found, through content analysis, the existence of 215 complaints, classified into three categories of conflicts: Transgression of the law, Institution and Residents themselves. It was also found that the coexistence problems were the main triggers of conflicts and that most conflicts were not resolved, leading to dissatisfaction with the social relations and loneliness of students in student housing. The second article is in the field of psychometry and aimed to elaborate a Student Housing Conflict Resolution Strategies scale (ERCME), gathering evidence of factorial validity and internal consistency, based on the exploratory study. Two studies were conducted with students residing in housings of public universities in Paraíba state. In Study 1, after the elaboration of the ERCME, the scale was applied in 200 residents (Mage=23; SD=4,20). The exploratory analysis revealed a three-factor structure: Aggressive Strategy, Assertive Strategy and Submissive Strategy, with an internal consistency indicator above recommended. Study 2 consisted of a new sample of 200 residents (Mage=23 years; SD=3,04). Through confirmatory factor analysis, it was observed that the three-factor structure represented the best alternative, observing meritorious adjustment indicators [χ² (101) = 176,860, p < 0,001, χ²/gl=1,751, CFI= 0,90, GFI = 0,90, TLI = 0,88 e RMSEA = 0,06 (IC90% = 0,04 – 0,07)]. It was concluded that the ERCME is a reliable and adequate instrument to assess the conflict resolution strategies of students who live in student housing, enabling its use in research on this topic. In order to understand the psychological processes involved in conflict resolution strategies in the context of student housing, the third article tested a theoretical model that explains the set of associations between sociomoral variables: empathic concern, personal distress, perspective taking, fantasy, moral judgment of justice and the three conflict resolution strategies – assertive, aggressive and submissive. A total of 394 college students living in student housing participated in this study (Mage=24.02, SD=3.43). Through Structural Equation Modeling, it was found that the results confirmed the central hypothesis that the dimensions of empathy and justice were related to different ways of resolving conflicts. It was also identified that the higher the level of moral judgment of justice, the lower the chance of the individual to be submissive in conflicting situations. (χ²(12)=12.225; p=0.428; χ²/g.l= 1.019; GFI=0.991; AGFI=0.979; CFI=0.998; RMSEA=0.07). Thus, this study showed the importance of using developmental psychological dimensions to understand the conflict resolution process and contributed to its expansion to broader social contexts. Furthermore, the results of this study may contribute to the elaboration of interventionist activities that promote more assertive and pro-social conflict resolution strategies in student housing.